Toxicological evaluation of cooked lima beans using duck embryos - Carillo, Leah Fe C.; Dumelod, Benelyn Domingo (1999., 1999)
The study aimed at evaluating the effects of commonly used cooking preparations on the toxicity of lima beans. Phase I dealt with the determination of the optimum cooking time for lima beans. Sensory evaluation was done to assess the texture and acceptability of texture of the lima beans cooked separately for 1, 1 1/2 and 2 hours. Sensory evaluation showed no significant difference in the acceptability of texture of lima beans cooked for 1, 1 1/2 and 2 hours. For practical purposes, the selected cooking time was one hour. In Phase II, extracts were made from cooked lima beans. In Treatment A, the beans were soaked overnight prior to cooking. In Treatment B, the cooking water used was drained after the first half of the cooking period after which the beans were re-boiled for the remaining half using a new batch of cooking water. In Treatment C, the beans were cooked continuously. The total cooking time used in each treatment was based on the optimum cooking time determined in Phase I. The different extracts were inoculated into five-day old duck embryos. Three sets of control were used -- closed, open and water. The first two were uninoculated while the last was treated with distilled water instead of lima bean extracts. Three trials were made and 20 duck embryos were used per treatment in each trial. After four days, the number of viable duck embryos were taken. Results showed that cooing alone is not as effective in reducing toxicity as soaking prior to cooking and replacing the cooking water halfway through the cooking period.
Thesis (BSFT)-- University of the Philippines Diliman
Keywords: Beans; Food -- Toxicology